Analysis and disclosure factors for sustainability reporting on web pages of peruvian listed companies - Hernández-Pajares, Julio César (2021)
The objective of this research is to analyze the sustainability information published on corporate websites and study the factors that determine the level of disclosure of this information in Peruvian listed companies for the year 2018. For this purpose, the study conducted a content analysis of web pages of 151 listed companies to establish a compliance index of sustainability information and examined whether the variables size, profitability, transnational nature and type of business activity were significant in this index. The results found that in the web pages, not all the disclosure criteria established are met. The size and type of business were determining factors. It is concluded that the level of information does not reach full compliance with international information standards or mandatory regulations, companies with greater resources and sectors with greater environmental impact present greater disclosure.